DETERMINANTS OF GOOD CORPORATE GOVERNANCE, FIRM SIZE, PROFITABILITY, AND LEVERAGE ON EARNING QUALITY - Pariang Siagian; Amalia Lita; Lusianah Lusianah (Journal of Applied Finance & Accounting, 2022)
Earnings management as a financial statement manipulation is not a new issue in the existing business. Yet, conducting income smoothing is suspected of keeping going in preparing the financial reports in specifying the profit with trickery. This paper wants to examine the determinants of some variables on earnings quality by employing the empirical data obtained from go public manufacturing companies’ periods of 2018 to 2020 in Indonesia. This study uses multiple linear regression to analyze, which is processed in accordance with the research purpose. The results achieved are some of the independent variables, namely Good corporate Governance, Company Size, and Leverage do not affect earnings quality, while Profitability does not significantly affect earning quality. The findings have important implications for company managers, better performance, and policymakers and provide useful information to assist the potential to invest, not only focusing on the profit reported without considering the other factors disclosed in the financial statements.